2003
DOI: 10.1007/bf02483449
|View full text |Cite
|
Sign up to set email alerts
|

The expression of matrix metalloproteinase-2 and-9 in human gliomas of different pathological grades

Abstract: Matrix metalloproteinases (MMPs) have been implicated to play a critical role in glioma invasiveness. In this study, we aimed to investigate the expression of MMP-2 and MMP-9 in human gliomas of different degrees of malignancy, and evaluated the correlation between MMP-2 and MMP-9 expression in gliomas. The samples from 65 cases of glioma were divided into four groups according to the WHO classification: there were 16 cases of grade I, 17 cases of grade II, 20 cases of grade III, and 12 cases of grade IV. Norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
115
1
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(130 citation statements)
references
References 26 publications
8
115
1
4
Order By: Relevance
“…The glioma vasculature as well as infiltrating inflammatory cells, which form a portion of the glioma mass have been implicated in MMP expression (VanMeter et al 2001). Strong gelatinase expression correlates with tumor grade (Forsyth et al 1999, Wang et al 2003. Intracranial implantation of glioblastoma cells in nude mice resulted in increased levels of MMP-9 during growth (Sawaya et al 1998, Chintala et al 1999).…”
Section: Mmps In Gliomamentioning
confidence: 99%
“…The glioma vasculature as well as infiltrating inflammatory cells, which form a portion of the glioma mass have been implicated in MMP expression (VanMeter et al 2001). Strong gelatinase expression correlates with tumor grade (Forsyth et al 1999, Wang et al 2003. Intracranial implantation of glioblastoma cells in nude mice resulted in increased levels of MMP-9 during growth (Sawaya et al 1998, Chintala et al 1999).…”
Section: Mmps In Gliomamentioning
confidence: 99%
“…Gelatinases, particularly matrix metalloproteinase-2 (MMP-2), can be considered the prime factor in glioma invasiveness, since it can break down the basement membrane ECM components such as collagen type IV and laminin. MMP-2 expression also correlates with the progression and the degree of malignancy of gliomas [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that MMP-2 is localized in both tumor and vasculature cells, indicating multiple roles for this molecule in tumor progression, including angiogenesis (Sawaya et al, 1996;Forsyth et al, 1999). MMP-2 expression is also known to associate with tumor invasion, angiogenesis, metastasis and recurrence (Wang et al, 2003;Chambers andMatrisian, 1997, Komatsu et al, 2004).…”
Section: Introductionmentioning
confidence: 99%